The Effects of Early Institutionalization on the Discrimination of Facial Expressions of Emotion in Young Children - Jeon, Hana (Infancy, 2010)
The current study examined the effects of institutionalization on the discrimination of facial expressions of emotion in 3 groups of 42-month-old children. One group consisted of children abandoned at birth who were randomly assigned to Care as Usual (institutional care) following a baseline assessment. Another group consisted of children abandoned at birth who were randomly assigned to high-quality foster care following a baseline assessment. A third group consisted of never-institutionalized children who were reared by their biological parents. All children were familiarized to happy, sad, fearful, and neutral facial expressions and tested on their ability to discriminate familiar versus novel facial expressions. Contrary to our prediction, all three groups of children were equally able to discriminate among the different expressions. Furthermore, in contrast to findings at 13–30 months of age, these same children showed familiarity rather than novelty preferences toward different expressions. There were also asymmetries in children’s discrimination of facial expressions depending on which facial expression served as the familiar versus the novel stimulus. Collectively, early institutionalization appears not to impact the development of the ability to discriminate facial expressions of emotion, at least when preferential looking serves as the dependent measure. These findings are discussed in the context of the myriad domains that are affected by early institutionalization.